Sistem Informasi Geografis Pemetaan Jalan Desa Berbasis Web - Gede Sri Handayani, Luh; Piarsa, I Nyoman; Suar Wibawa, Kadek (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.2 Agustus 2015, 2015)
Village roads is one of the critical infrastructure that is used to connect a village area with the other villages. Information of the village road is also an important thing to be known, but is not matched with the data collection are still not done enough. That is because the number of village roads and collecting data are still done manually, made it difficult to collect data efficiently, so that the need for a digital system for collecting data more quickly. Geographic Information Systems Mapping Village Road is a Web-based digital system that can be used to mapping village road using Google Maps, polyline feature to describe a network of roads and Geometry Library to count length of road. This system can collect data of village roads in two ways, namely digitization and input the coordinates that can be done by the operator, while the admin can do data processing on the data master. Results of data collection of village roads can provide information to the user about street name, road length, type of road surface and road condition.
Keywords: Jalan Desa, Pendataan Jalan, Sistem Informasi Geografis, Berbasis Web